Greater tumen region cooperation : obstacles in Northeast Asia regionalism? - Liu, Shuguang (2012)
The advancement of cross-border transport infrastructure in the Greater Tumen Region (GTR) marks the progress of multilateral cooperation in Northeast Asia. But the different interests and approaches among the relevant parties are injecting uncertainties into the sub-regional initiative.